Adversity Quotient, Religious Spirituality, and Career Adaptability: An Empirical Study on Masters Students of Islamic Religious Education - Nurma Millatina; Rahmat Aziz; Indah Aminatuz Zuhriyah (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
This study aims to analyze the effect of Adversity Quotient (AQ) on Career Adaptability (CA) and to examine the role of Spiritual Religious (SR) as a moderating variable in this relationship. The scope of the research focuses on students of the Master of Islamic Education (MPAI) program at the State Islamic University (UIN) Maulana Malik Ibrahim Malang, who are facing academic challenges and preparing for careers in Islamic education. This research employed a quantitative explanatory approach. The sample consisted of 164 students selected using total sampling technique. The research instrument was a Likert-scale questionnaire that had been tested for validity and reliability. Data were analyzed using the Structural Equation Modeling–Partial Least Square(SEM-PLS) method via SmartPLS 4. The results showed that AQ had a positive and significant effect on CA (β = 0.683; p < 0.001). However, SR did not have a significant direct effect on CA (β = 0.066; p = 0.175), nor as a moderating variable (β = 0.070; p = 0.180). Simultaneously, AQ and SR explained 47.1% of the variance in CA. The study concludes that AQ is a key factor in shaping students' career adaptability, while SR serves more as a source of internal motivation rather than a statistically significant predictor. This research recommends strengthening students’ personal resilience through psychological and spiritual approaches within Islamic education.